Risk Contracts with Private Information and One-Sided Commitment - Pedro Hemsley; Eduardo Zilberman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2015)
In a repeated unobserved endowment economy in which agents negotiate long- term contracts with a financial intermediary, we study the implications of the interaction between incentive compatibility and participation constraints for risk sharing. In particular, we assume that after a default episode, agents consume their endowment and remain in autarky forever (one-sided commitment). We find that, once away from autarky today, if the probability of drawing the highest possible endowment shock is small enough, the optimal contract prevents agents from reaching autarky tomorrow and, thus, from being ". Moreover, an invariant cross-sectional distribution of life-time utilities (or values) exists. Our numerical simulations suggest that the mass of agents living in autarky is zero in the limit.
Keywords: D31; D82; D86; 330; risk sharing contracts; private information; one-sided commitment